Legba, the Adolescent ofVoodoo in Benin: Role in Social Regulation - FIOSSI KPADONOU, EMILIE ABLAWA; Djidonou, ANSELME; ALIGNONON, SEGBEDE; KPADONOU GODONOU, TOUSSAINT; KINOO, PHILIPPE; AGOSSOU, THÉRÈSE ANTOINETTE. A.; HAYEZ., JEAN YVES (My University, 2017)
Abstract: Divinities (voodoos) are a common reality in Benin. Lègba is a particularly familiar divinity in the central and southern parts of Benin. Objective: analyze the possibilities of using the mie and attributes of Lègba while carrying out psychiatric therapy teenagers. Method: Observations, together with guided discussions were carried out belWeen 2009 and 2012 with 25 resource persons in the Beninese towns of Porto-Novo, Ouidah, Abomey, Zogbodomé and Cotonou. Results: Lègba is the messenger, guide and interpreter for other voodoos; he keeps guard over the border belWeen the world of the gods (spirits) and that ofhumans. His name expresses "pulling down and breaking; pursuing, killing and destroying; reconstructing". Lègba is the phallic god of the Fon tribe in Benin; his sexual organ, in full erection, is exposed with an exaggerated length. He is often found in houses, but especially at the thresholds of homes, road junctions, market centers and at the entrances of towns and villages. Lègba is said to be very intelligent and cunning; full ofideas on vengeance, perseverance, insight and shrewdness; full of force, ardor, violence; and dreadfully aggressive. Discussion and conclusion: Given his position and status, Lègba is unavoidable despite his behavior which is rather disturbing in severa! aspects. He is an expression of force, life, serenity, organization and communication. He reassures the youths, exculpates sexuality and brings about a feeling of security on issues of virility. As such, a good understanding of the role and characteristics of Lègba can be useful in therapy, especially in situations where simple words cannot explain certain behaviors (of the patients or their relatives) which then need to be readjusted or deciphered otherwise.
Keywords: Keywords: divinity; behavior; sexuality; security